In What Ways Do Synthetic Nucleotides and Natural Base Lesions Alter the Structural Stability of G-Quadruplex Nucleic Acids? - Janos Sagi (Journal of Nucleic Acids)
Synthetic analogs of natural nucleotides have long been utilized for structural studies of canonical and noncanonical nucleic acids, including the extensively investigated polymorphic G-quadruplexes (GQs). Dependence on the sequence and nucleotide modifications of the folding landscape of GQs has been reviewed by several recent studies. Here, an overview is compiled on the thermodynamic stability of the modified GQ folds and on how the stereochemical preferences of more than 70 synthetic and natural derivatives of nucleotides substituting for natural ones determine the stability as well as the conformation. Groups of nucleotide analogs only stabilize or only destabilize the GQ, while the majority of analogs alter the GQ stability in both ways. This depends on the preferred syn or anti N-glycosidic linkage of the modified building blocks, the position of substitution, and the folding architecture of the native GQ. Natural base lesions and epigenetic modifications of GQs explored so far also stabilize or destabilize the GQ assemblies. Learning the effect of synthetic nucleotide analogs on the stability of GQs can assist in engineering a required stable GQ topology, and exploring the in vitro action of the single and clustered natural base damage on GQ architectures may provide indications for the cellular events.